Growth performance and incidence of skeletal anomalies in pacu larvae under different weaning protocols - de Freitas, Thiago Mendes; Lopes, Ivã Guidini [UNESP]; Lopes, Taís da Silva; Buzollo, Hellen [UNESP]; Portella, Maria Célia [UNESP] (Boletim do Instituto de Pesca, 2019)
The inadequate supply of food during a fish’s larval stage, in addition to impairing growth and survival, may lead to the emergence of skeletal anomalies, since essential nutrients are involved in the osteogenic process. The aim of this study was to evaluate the effects of two weaning periods on growth, survival and incidence of skeletal anomalies in pacu larvae (Piaractus mesopotamicus) during its initial development. The larvae (5 dph) were placed in 100L tanks at a density of 12 larvae L-1, during 42 days. The experiment was conducted in a completely randomized design with four feeding treatments: (A) larvae fed only Artemia nauplii; (D) larvae fed only formulated diet; and two treatments with different weaning periods, early at six (W6) and late, at twelve days of feeding (W12). Higher growth indexes and survival rates were observed in A and W12, in comparison to W6 and D. At the end of the experiment, larvae fed Artemia nauplii and subjected to late weaning (W12) presented higher mass gain and survival, in comparison to W6 and D, however the incidence of skeletal anomalies was similar among treatments. It was concluded that the emergence of skeletal anomalies in P. mesopotamicus larvae was not associated to the weaning protocols used in this study and late weaning, at 12 days of feeding, did not impair growth and survival of these larvae.
Desempenho e incidência de anomalias esqueléticas em larvas de pacu sob diferentes protocolos de transição alimentar
Keywords: Intensive larviculture; Piaractus mesopotamicus; Skeletal anomalies; Weaning